Safety, Tolerability, and Efficacy of Overnight Switching From Sildenafil to Tadalafil in Patients With Pulmonary Arterial Hypertension. Issue 5 (12th September 2013) - Shapiro, Shelley; Traiger, Glenna; Hill, Wendy; Zhang, Lixia; Doran, Aimee K.
Summary: Aims: Tadalafil, a once‐daily phosphodiesterase type 5 inhibitor (PDE‐5I), offers clinicians an alternative to sildenafil, a 3‐times‐daily (t.i.d.) PDE‐5I for treatment of pulmonary arterial hypertension (PAH). However, there are limited data describing the risks and benefits or recommended methodology of switching patients from sildenafil to tadalafil. Methods: Chart reviews were conducted on all World Health Organization group 1 patients on sildenafil for ≥3 months who transitioned to tadalafil with documented clinic visits and 6‐min walk tests on both drugs. Most patients were transitioned by discontinuing sildenafil after the evening dose and initiating tadalafil 40 mg/day the next day. Data collected included demographics, PAH etiology, diagnostic hemodynamics, 6‐min walk distance (6MWD), PDE‐5I side effects, and concomitant medications. Data on B‐type natriuretic peptide (BNP) levels were available for most patients also receiving endothelin receptor antagonists (ERAs). Results: Medical records from 98 patients were evaluated. Most patients (92%) were on sildenafil for >1 year, and 78% were receiving sildenafil 80–100 mg t.i.d. Ninety‐seven percent of patients (95/98) were successfully transitioned and maintained on 40 mg/day. With a mean duration on tadalafil therapy of 243 ± 127 days at the time of analysis, 6MWD was unchanged. Patient‐reported adverse events included headache (4%) and heartburn (2%). There was minimal change in BNP levels in the subset of patients receiving an ERA concomitantly. Conclusions: Transition from sildenafil to tadalafil 40 mg/day appears feasible without clinical deterioration or intolerable side effects. This study provides guidance to physicians considering transition from sildenafil to tadalafil for selecting patients.